Volunteering experience during emergencies: Comparative analysis of a military operation and a pandemic - Kulik, PhD, Liat (Journal of Emergency Management, 2022)
The aim of this study was to investigate differences in the volunteering experience in two states of emergency in Israel: Operation Protective Edge (a military man-made emergency) and the first wave of the COVID-19 pandemic (a natural emergency). The sample included 993 volunteers, of whom 498 volunteered during Operation Protective Edge and 504 during the COVID-19 pandemic. A quantitative research design was used to investigate three aspects of the volunteering experience: motives for volunteering, satisfaction from volunteering, and commitment to volunteer. Social solidarity was the most prominent motive for volunteering in both emergencies. The level of the egoistic motives, the intrinsic satisfaction from volunteering, and long-term commitment to volunteering were higher during the COVID-19 pandemic than among the volunteers during the military operation. We used a qualitative research design to investigate the experience of special moments in volunteering. The profile of special moments experienced by the COVID-19 volunteers combined self and client experiences, whereas among Operation Protective Edge volunteers, special moments are reflected mainly in experiences related to the clients and the community.